Sustainability of waste picker sustainopreneurs in Pakistan's informal solid waste management system for cleaner production. (10th September 2020) - Yousafzai, Muhammad Tariq; Nawaz, Muhammad; Xin, Chunlin; Tsai, Sang-Bing; Lee, Chien-Hung
Abstract: This study aims to advocate for the acknowledgment of the services of invisible hands that do pro-environmental work, despite living in post-conflict trauma themselves. These "accidental sustainopreneurs" earn a living while helping societies become more sustainable. Their work for both upstream manufacturers and downstream consumers serves as a stepping stone toward the introduction of cleaner production across waste value chains in developing countries. They have positive effects on multiple recycling sectors, and their transition to formal, integrated solid waste management is the objective of this study. Inductive qualitative research design is employed to examine how these entrepreneurial agents work in unpredicted ways to create value for society while being stigmatized by focusing specifically on the case of waste picker sustainopreneurs registered with the Water and Sanitation Services in Pakistan (WSSP). The findings of this study suggested that a whopping 99% majority of such workers pretend as if none of their kind exist, possess dual identities, and are stigmatized due to refugee backgrounds. Using the social construction of stigma lens, their identities have been stigmatized amidst their burden of complementing the work of local MSWM authorities. In addition, the findings regarding unpredictable weather patterns, lack of assets, seasonal shocks, uncertain policies, rules of business, and the exploitative subletting of waster picker jurisdictions are reported. This study provides a more thorough understanding of their self-organized work context, an understanding of policies, and the higher survival skills and immunity levels of these workers, even in the absence of safety equipment and measures. This study demonstrates how self-organizing, low-tech, informal solutions can act as a foundation toward cleaner productions and environmental sustainability.